Examining c-di-GMP and possible quorum sensing regulation in pseudomonas fluorescens SBW25: Links between intra- and inter-cellular regulation benefits community cooperative activities such as biofilm formation - Moshynets, OV; Foster, D; Karakhim, SA; McLaughlin, K; Rogalsky, SP; Rymar, SY; Volynets, GP; Spiers, AJ (National Academy of Sciences of Ukraine and Palladin Institute of Biochemistry of the National Academy of Sciences of Ukraine, 2018)
Bacterial success in colonizing complex environments requires individual response to micro-scale conditions as well as community-level cooperation to produce large-scale structures such as biofilms. Connecting individual and community responses could be achieved by linking the intracellular sensory and regulatory systems mediated by bis-(3′-5′)-cyclic dimeric guanosine monophosphate (c-di-GMP) and other compounds of individuals with intercellular quorum sensing (QS) regulation controlling populations. There is growing evidence to suggest that biofilm formation by many pseudomonads is regulated by both intra and intercellular systems, though in the case of the model Pseudomonas fluorescens SBW25 Wrinkly Spreader in which mutations increasing c-di-GMP levels result in the production of a robust cellulose-based air-liquid interface biofilm, no evidence for the involvement of QS regulation has been reported. However, our recent review of the P. fluorescens SBW25 genome has identified a potential QS regulatory pathway and other QS–associated genes linked to c-di-GMP homeostasis, and QS signal molecules have also been identified in culture supernatants. These findings suggest a possible link between c-di-GMP and QS regulation in P. fluorescens SBW25 which might allow a more sophisticated and responsive control of cellulose production and biofilm formation when colonising the soil and plant-associated environments P. fluorescens SBW25 normally inhabits.